A Lie Theory-Based Control Scheme for a Solar-Fed Encoderless SPMSM - Abirami Kalathy; Arpan Laha; Praveen Jain; Majid Pahlevani (IEEE Open Journal of Power Electronics)
This article proposes a novel Lie group controller for speed sensorless control of a surface-mounted Permanent Magnet Synchronous Motor (SPMSM) fed by a solar microinverter. Solar-fed motor drive poses significant challenges due to the inherent solar power fluctuations and small storage capability of solar microinverters. Thus, the reliable operation of a solar-powered motor drive requires a control methodology that delivers optimal performance for the fluctuating solar power along with fast dynamic behavior to handle source/load transients. The proposed control strategy quickly modulates the drive frequency based on Lie theory in response to any transients, maximizing the motor's torque output. The proposed control method has better dynamic performance, ease of start-up, and is simpler to implement compared to existing observer-based vector control methods. Theoretical analysis as well as simulation and experimental results prove the effectiveness of the proposed control method.